Effect of Sow Lactation Crate Size on Litter Performance and Survivability - L. L. Thomas; K. F. Coble; C. W. Hastad; M. D. Tokach; S. S. Dritz; R. D. Goodband; J. M. DeRouchey; J. C. Woodworth (Kansas Agricultural Experiment Station Research Reports, 2017)
A total of 529 litters of pigs (PIC TR4 × (Fast LW × PIC L02)) were used to examine the effect of sow lactation crate size on nursing pig litter performance and survivability. The sow portion of the farrowing crate was maintained at a constant length and width of 7.4 and 2.0 ft, respectively. To form the treatments, crate width was adjusted accordingly, taking space away from one sow’s crate to give it to another allowing for 3 crate widths: 4.8 (small), 5.4 (medium), and 6.0 ft (large). This allowed for blocks of 3 crates, where each treatment was represented. Sows were loaded into individual lactation crates at random, balancing for parity across treatments. Cross fostering occurred within 24 h of farrowing prior to obtaining d 1 litter weight in effort to equalize litter size across treatments. Data were analyzed using generalized mixed models where treatment was a fixed effect and block was a random effect. Born alive, piglets weaned, and pre-weaning mortality, were all fitted using a binomial distribution. Regardless of treatment, there was no evidence of differences in total piglets born (14.3), percentage of piglets born alive (92.3%), d 1 litter weight after cross fostering (40.0 lb), litter weaning weight (145.9 lb), litter ADG (5.4 lb/d), or number of piglets weaned (10.7). In addition, no evidence for differences was observed in the percentage piglets weaned (80.9%) or pre-weaning mortality (19.1%). In conclusion, increasing lactation crate size did not impact litter performance or pig survivability in this study.
Keywords: lactation; lactation crate size; sow